2023
DOI: 10.3389/fphar.2023.1242109
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine exposure drives cell cycle exit and aberrant differentiation in rat hippocampal-derived neurospheres

Shaomin Wang,
Liang Wang,
Qian Bu
et al.

Abstract: Introduction: Methamphetamine (METH) abuse by pregnant drug addicts causes toxic effects on fetal neurodevelopment; however, the mechanism underlying such effect of METH is poorly understood.Methods: In the present study, we applied three-dimensional (3D) neurospheres derived from the embryonic rat hippocampal tissue to investigate the effect of METH on neurodevelopment. Through the combination of whole genome transcriptional analyses, the involved cell signalings were identified and investigated.Results: We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Additionally, METH induced novel networks of astrocytespecific gene expression that control cytokine responses and the inflammasome, resulting in modifications to the RNA and protein levels of neuroinflammatory and cytokine gene expression [66]. After being exposed to METH, neutrospheres made from embryonic rat hippocampal tissue displayed abnormal cell differentiation in both neurons and astrocytes, as well as a decreased capacity for neutrosphere migration coupled with an increase in oxidative stress and apoptosis [67]. Taken together, the scRNA-seq literature overview demonstrated that COC mainly influences neurons in VTA and NAc, while METH has a primary influence on the immune response.…”
Section: Identifying Cell Populations By Molecular Clusteringmentioning
confidence: 99%
“…Additionally, METH induced novel networks of astrocytespecific gene expression that control cytokine responses and the inflammasome, resulting in modifications to the RNA and protein levels of neuroinflammatory and cytokine gene expression [66]. After being exposed to METH, neutrospheres made from embryonic rat hippocampal tissue displayed abnormal cell differentiation in both neurons and astrocytes, as well as a decreased capacity for neutrosphere migration coupled with an increase in oxidative stress and apoptosis [67]. Taken together, the scRNA-seq literature overview demonstrated that COC mainly influences neurons in VTA and NAc, while METH has a primary influence on the immune response.…”
Section: Identifying Cell Populations By Molecular Clusteringmentioning
confidence: 99%